Effects of injection of morphine into head of caudate nucleus on activities of neurons of nucleus raphe magnus in rats - ZHU Bing; LIU Xiang (Acta Pharmacologica Sinica, 2016)
After microinjections of morphine (10μl/1μl on each side) into the anterior part of the head of nucleus caudatum, an obvious and prolonged inhibitory effect on nociceptive response of NRM neurons (n=23) was seen for 2-30 min. This effect of some neurons lasted 90-120 min. In addition, it inhibited the spontaneous firing of the majority of NRM neurons. When morphine was injected into the posterior part of the head of n. caudatem (n=21), the firing rate and nciceptive response of the majority of neurons were not much altered. In cpmparison with the rats injected morphine into the abterior part, the difference was significant during 2-30 min. There was no marked difference as compared with the control group injected saline. These results indicate that morphine can induce a pronounced inhibitory effect upon the nocicptive response of the majority of NRM neurous only when injected into the anterior part of the head of n. caudatum.